Cardiovascular and renal effects of hyperuricaemia and gout - R. Pontremoli; G. Leoncini; F. Viazzi (PAGEPress Publications, 2012)
A number of epidemiological studies have reported an association between serum uric acid levels and a wide variety of high-risk conditions including hypertension, insulin resistance, and kidney and cerebro-cardiovascular disease. All things considered, serum uric acid may induce cardiovascular and kidney events both directly and indirectly by promoting other well-known mechanisms of damage. While asymptomatic hyperuricemia is currently not considered to be an indication for urate lowering therapy, there is growing evidence indicating a linear relationship between pharmacological reduction in serum uric acid and incidence of cardiovascular and renal events.